VISIBLE RANGE PHOTOCATALYSTS FOR SOLID PHASE PHOTOCATALYTIC DEGRADATION OF POLYETHYLENE AND POLYVINYL CHLORIDE - Apeksha Gupta; Y. N. Lakshmi; R. Manivannan; S. Noyel Victoria (Journal of the Chilean Chemical Society, 2017)
Solid phase photocatalytic degradation of polyethylene (PE) and polyvinyl chloride (PVC) with various photocatalysts such as ceria annealed at 350°C and 850°C, zinc oxide annealed at 250°C, copper sulfide and titania particles was studied under different light sources. Except titania, all the other photocatalysts performed reasonably well both in the visible and ultra-violet (UV) radiations. Ceria annealed at 850°C showed degradation efficiencies higher than 70% for PVC in the fluorescent and solar radiation. Ceria annealed at 350°C showed degradation efficiencies higher than 75% for polyethylene in fluorescent, solar and UV radiation. The Fourier transform infrared spectroscopy studies show the presence of adsorbed carbon dioxide on the degraded polymer- photocatalyst composite films. The UV-visible spectroscopic studies show that the ceria, zinc oxide and copper sulfide photocatalysts are active in the visible spectrum resulting in enhanced degradation efficiency in fluorescent and solar radiation.